Dynamic displacement measurement of a wind turbine tower using accelerometers: tilt error compensation and validation - C. Jonscher; P. Helming; D. Märtins; A. Fischer; D. Bonilla; B. Hofmeister; T. Grießmann; R. Rolfes (Wind Energy Science)
For vibration-based structural health monitoring (SHM) of wind turbine support structures, accelerometers are often used. Besides the structural acceleration, the measured quantity also contains the acceleration component due to gravity, which is known as tilt error. This tilt error must be quantified and taken into account; otherwise it can lead to incorrect evaluations, especially in the fatigue estimation or the dynamic displacement estimation using accelerometers. The standard solution is to explicitly measure the tilt angle, which requires an additional sensor for each measurement point and is not applicable for already recorded measurements without tilt information. Therefore, a novel tilt error compensation method is presented by using the static bending line. As a result the influence of the tilt error can be estimated in advance, and no additional sensors for tilt measurement are needed.